PENERAPAN KURIKULUM MERDEKA DI MADRASAH TSANAWIYAH - HARTONO, HARTONO; PEMBANGUNAN, HELDY RAMADHAN PUTRA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT The implementation of Merdeka Curriculum at MTs Negeri 15 Boyolali aims to create a learning environment that is adaptive and oriented to student needs. This research was conducted because there is still a lack of studies related to the implementation of the Independent Curriculum in madrasas, including the readiness of teachers who require specific training and the lack of in-depth understanding of the responses of students and parents who tend to still have a traditional mindset, so this study aims to explore three main aspects, namely teacher readiness, differentiated learning, and preparation of learning tools. Teacher readiness is improved through training and workshops, which focus on understanding the concepts of Merdeka Curriculum and applying innovative learning methods. Differentiated learning is implemented by grouping students based on ability and interest, and using varied methods to create relevant and interesting learning experiences. In addition, learning tools are arranged flexibly, including the flow of learning objectives and teaching modules. This research uses qualitative methods, with data collection techniques of interviews, classroom observations and document studies. The results of this study show that the application or implementation of this curriculum is less than optimal due to several faktors. This research is expected to provide solutions to some of the problems found so that the implementation of this curriculum can be maximized in Madrasah. ABSTRAK Penerapan Kurikulum Merdeka di MTs Negeri 15 Boyolali bertujuan untuk menciptakan lingkungan belajar yang adaptif dan berorientasi pada kebutuhan siswa. Penelitian ini dilakukan karena masih minimnya kajian terkait penerapan Kurikulum Merdeka di madrasah, termasuk kesiapan guru yang membutuhkan pelatihan spesifik serta kurangnya pemahaman mendalam tentang respon siswa dan orang tua yang cenderung masih berpola pikir tradisional, sehingga penelitian ini bertujuan untuk mengeksplorasi tiga aspek utama, yaitu kesiapan guru, pembelajaran berdiferensiasi, dan penyusunan perangkat pembelajaran. Kesiapan Guru ditingkatkan melalui pelatihan dan workshop, yang berfokus pada pemahaman konsep Kurikulum Merdeka dan penerapan metode pembelajaran inovatif. Pembelajaran berdeferensiasi diterapkan dengan pengelompokan siswa berdasarkan kemampuan dan minat, serta penggunaan metode yang bervariasi untuk menciptakan pengalaman belajar yang relevan dan menarik. Selain itu, perangkat pembelajaran disusun secara fleksibel, mencakup alur tujuan pembelajaran dan modul ajar. Penelitian ini menggunakan metode kualitatif, dengan teknik pengumpulan data wawancara, observasi kelas dan studi dokumen. Hasil dari penelitian ini menunjukkan bahawa penerapan atau implementasi kurikulum ini kurang maksimal disebabkan beberapa faktor. Penelitian ini diharapkan dapat memberikan solusi atas beberapa masalah yang ditemukan agar implementasi kurikulum ini bisa lebih maksimal di Madrasah.